Bentuk-Bentuk Tindak Tutur Ekspresif Karikatur Pan Kote dalam Koran Denpost - Sofie Mahmudah; I Wayan Simpen; I Wayan Teguh (Udayana University, 2022)
This article discusses the forms of expressive speech acts in the Pan Kote caricature of the Denpost 2019 newspaper. Pan Kote is classified as a verbal caricature with the use of complex speech in it. The complexity of speech in Pan Kote's caricature isinteresting to study with a pragmatic approach, especially expressive speech acts. As the essence of expressive speech acts, that is, it serves to convey the psychological feelings of the speaker to the speech partner or vice versa in certain speech situations. It is these aspects that are tried to be explored in this article. The problem in this study is to find out the forms of expressive speech acts of Pan Kote's caricature in the Denpost newspaper. The theory used is pragmatic theory, especially speech act theory, referring to the expert view, namely Searle (1969). The method used is descriptive qualitative. The results showed that 47 data were found out of a total of 73 data included in the form of expressive speech acts. The forms of expressive speech acts are grouped into 11 forms consisting of satire (17 data), criticize (9 data), complain (11 data), congratulate (1 data), prohibit (1 data), criticize (2 data) , ordered (1 data), surprised (1 data), worried (2 data), agreed (1 data), and grateful (1 data).